Policy of Ulama Consultative Council in Government Politics at Lhokseumawe - Muhammad Muhammad; Sukiman Sukiman; Irwansyah Irwansyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The aim of this research is to know the roles and the functions of Ulama Consultative Council in Government at Lhokseumawe, Aceh, Sumatera. The method is used qualitative research to get and to develop the data and result. The result is found that the role of the Ulama Consultative Council in government politics in Lhokseumawe City can be grouped into two forms, namely the role of consideration and function in establishing legal edicts. Ulama Consultative Council functions optimally in providing consideration / suggestions / suggestions to local governments. The function of determining legal edicts, where Ulama Consultative Council oversees the administration of government, development and community development, then the results of supervision can be issued in the form of legal edicts submitted to local governments and also disseminated to the public.